Case study evaluation past, present and future challenges - Russell, Jill.; Greenhalgh, Trisha; Kushner, Saville (Bingley, U.K. : Emerald, 2015)
In todays world, with its preoccupation with impact assessments and results-based management, program evaluation is all too often framed as an affirmation of an official narrative rather than as a source of alternatives. The power of case study is its insistence on opening up rather than suppressing the complexity of social programs, on documenting multiple voices and exploring contested viewpoints. In this way, case study resists the trend towards evaluations that simply focus on what works, that reduce the complexity of social life to a single narrative, and to formulations that strip out most of what matters. Now more than ever, as government policies and programs orientate to global economic crisis and its impact on the lives of citizens and communities, we require evaluations that resist information loss and produce richness.
Case study, methodology and educational evaluation: a personal view / Clement Adelman -- Letters from a headmaster / Barry MacDonald -- Storytelling and educational understanding / Terry Denny -- Case study as antidote to the literal / Saville Kushner -- Thinking about case studies in 3-D : researching the NHS clinical commissioning landscape in England / Julia Segar, Kath Checkland, Anna Coleman, Imelda McDermott -- The case for evaluating process and worth : evaluation of a programme for carers and people with dementia / Samantha Abbato -- The collapse of "primary care" in medical education : a case study of Michigan's community/university health partnerships project / Brian McKenna -- 'Lead' standard evaluation / David Jenkins -- Freedom from the rubric / Robert Stake -- Twice-told tales? How public inquiry could inform n of 1 case study research / Trisha Greenhalgh -- Evaluation as the co-construction of knowledge : case studies of place-based leadership and public sector innovation / Jo Howard, Arturo Flores, Robin Hambleton -- Evaluation noir : the other side of the experience / Acacia Cochise, Saville Kushner.
Print version record
Keywords: Education -- Evaluation; Education -- General; Educational strategies & policy; Education; Education -- Evaluation